(untitled) (ASA, 2021)
Marriage is a very old worship. however, in domestic life there is bound to be conflict. So it can be said that it is impossible in one’s household life not to encounter conflict. But that’s where the reward field that must be passed by husband and wife. Domestic problems can arise from various directions. It can be from the person of each partner or from other family members. So sometimes as a result of conflict the household ship can be destroyed. Among them is early marriage. This research was written using a qualitative descriptive method, with a normative juridical approach where the author analyzed cases that had occurred in Indonesia related to early marriage. The results of the study stated that based on positive law, it is not permissible to marry at an early age. according to the maslahah perspective, early marriage should not be carried out because it causes harm. the limit of marriage age includes maslahah Al-hajiyât, namely the maslahah needed by humans whose position is to facilitate and eliminate difficulties